High-Resolution Urban Flood Forecasting by Using a Coupled Atmospheric and Hydrodynamic Flood Models - Chen, Guangzhao; Hou, Jingming; Zhou, Nie; Yang, Shaoxiong; Tong, Yu; Su, Feng; Huang, Lei; Bi, Xu (Frontiers in Earth Science, 2020)
Flood forecasting is one of the most significant tools for reducing flood risk and avoiding losses. To solve the problem of low resolution and short lead time of the traditional urban flood forecasting method, this work develops a novel high-accuracy and long leading time model through coupling the atmospheric and hydrological-hydrodynamic models. The GRAPE_MESO model is applied as atmospheric model predicting rainstorms. To improve the reliability, a reconstructed method is put forward to correct predicted rainstorm data. The reconstructed predicted rainstorm is then used as input data for the hydrodynamic flood model. Finally, the urban flood inundation process is forecasted by the coupled atmospheric and flood model. Though applying the coupled model at Fengxi New Town (China), the performance is evaluated for realistic urban flood forecasting. The results show that the coupled modeling system can predict satisfactory urban flood inundation process with high-resolution and long lead time.